If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying v = 2v + -73 Reorder the terms: v = -73 + 2v Solving v = -73 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. v + -2v = -73 + 2v + -2v Combine like terms: v + -2v = -1v -1v = -73 + 2v + -2v Combine like terms: 2v + -2v = 0 -1v = -73 + 0 -1v = -73 Divide each side by '-1'. v = 73 Simplifying v = 73
| 7n+6=13+7n | | 16=-2(x+4) | | 5-13w-6w^2=0 | | 4u+18=2u+66 | | 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) | | 6x+-9=2x+7 | | 17x-7=13x+1 | | 6x+-9=2x+-7 | | 3.2=y+5.4 | | 9x-(6x+9)=7x-29 | | 5m-4=3(m+6) | | 4a-7=7(a+1)+14a+6 | | t+30=1 | | 5-2(2m+3)=15 | | 2(10x+3)=5(4x-7) | | -23=5k+7k | | 0.6x=0.4x+50 | | 2(5-3x)=9-6x | | -7.6=5.3+x+7.34 | | 4x+6(x+40)=180 | | 6t-32=7t-50 | | 5c=c+52 | | 3(2x-8)=2(3x+8) | | 2(sqrt(x))-5=x | | 7x-1=2x-3 | | 5-3x=3x-25 | | 527=31n | | 2x-3=6+2x |